Management of the patient with fibromatosis of the left anterior chest wall - Subbaraj, Saravanakumar; Manohar, Sandeep (International Surgery Journal, 2020)
Desmoid fibromatosis is a rare but locally aggressive tumour comprised of myofibroblasts. It is histologically benign but can behave aggressively. They do not have the ability to metastasize but can cause significant morbidity and mortality by local invasion. These tumours may occur anywhere on the body, but are commonly found on the abdominal wall and within the intestinal mesentery. Mutations in either the β-catenin or the adenomatous polyposis coli (APC) genes are usually the cause for the development of desmoid tumours with the former comprising the sporadic development of tumours and the latter being associated with familial adenomatous polyposis syndrome. Surgical resection with histologically negative margins has been the cornerstone of therapy for this disease, but this paradigm has begun to shift. It is now common to accept a microscopically positive margin after resection as recurrence rates may not be significantly affected. This case report intends to describe the clinical, diagnostic and pathologic features of a post-traumatic fibromatosis involving left side chest wall in a 45 years old female and causing worsening pain. The surgical management was successfully undertaken.